Foundations of Robotics A Multidisciplinary Approach with Python and ROS - Herath, Damith; St-Onge, David (Springer Nature Singapore : Imprint: Springer, 2022)
This open access book introduces key concepts in robotics in an easy to understand language using an engaging project-based approach. It covers contemporary topics in robotics, providing an accessible entry point to fundamentals in all the major domains. A section is dedicated to introducing programming concepts using Python, which has become a language of choice in robotics and AI. The book also introduces the reader to the Robot Operating System (ROS), the ubiquitous software and algorithmic framework used by researchers and the industry. The book provides an inspired, up-to-date and multidisciplinary introduction to robotics in its many forms, including emerging topics related to robotics on Machine Learning, ethics, Human-Robot Interaction, and Design Thinking. The book also includes interviews with industry experts, providing an additional layer of insight into the world of robotics. The book is made open access through the generous support from Kinova Robotics. The book is suitable as an undergraduate textbook in a relevant engineering course. It is also suitable for students in art and design, high school students, and self-learners who would like to explore foundational concepts in robotics. "This book provides the 'foundation' for understanding how robots work. It is the accessible introduction that artists and engineers have been waiting for." - Ken Goldberg, William S. Floyd Jr. Distinguished Chair in Engineering, UC Berkeley.